If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16a-8(a+1)=3(a-3)
We move all terms to the left:
16a-8(a+1)-(3(a-3))=0
We multiply parentheses
16a-8a-(3(a-3))-8=0
We calculate terms in parentheses: -(3(a-3)), so:We add all the numbers together, and all the variables
3(a-3)
We multiply parentheses
3a-9
Back to the equation:
-(3a-9)
8a-(3a-9)-8=0
We get rid of parentheses
8a-3a+9-8=0
We add all the numbers together, and all the variables
5a+1=0
We move all terms containing a to the left, all other terms to the right
5a=-1
a=-1/5
a=-1/5
| 5000=200+2x | | 2y=14/3 | | 4z-3(z+1)=3(z-3)-2z | | 5000=200+b2 | | 12-8x+3x=6-2x | | 3v/2=42 | | .55x+.2x=x-15 | | .55x+.2x=x+15 | | 255x=x-1500 | | 3x-5=-x-16 | | .75x=x+15 | | x^2−15x=−50 | | x2−15x=−50 | | x^2+130x-3000=0 | | 5x-0.9=15 | | 7-6y=5 | | 12=6-1/2x | | b2-121=0 | | 1,2x=0.06 | | 8x^2-4x=-104 | | (X-1)(3x-7)=-1 | | x/6-(9x)/2=x/12 | | x/6-9x/2=x/12 | | x/6-9x2=x/12 | | 21+16m=165 | | 4x+6=4x+1 | | 25n-42=133 | | Y=1-(1-2x) | | -12+x/11=- | | 4(x-1)^2=28 | | 2x^2(9x^6)=0 | | -63=7n |